Safety Standard Of River Transportation (Speedboat) In Musi Port Of River Pasar 16 Ilir Palembang - Kodrat Alam (IWJ : Inland Waterways Journal, 2020)
South Sumatra is one of the provinces that has a large area of ​​water. Musi River is the main means of transportation in several sub-districts in South Sumatra. The problem discussed in this study is "What is the safety standard for river transportation passengers (speed boat) at Musi river Pasar 16 Ilir Palembang?" The purpose of this study was to determine the safety standards for river transportation (speedboat) passengers in the Musi River flow area at Pasar 16 Ilir, Palembang. The results of this study are expected to be useful for the teaching of literary readers, and for further researchers.1) for passengers, this research can be used as a reference in knowing passenger rights for safety in travel. 2) for the driver, this research can increase professionalism in driving, it can be used in increasing service to passengers and increasing professionalism of drivers and developing plans for the development of transportation infrastructure in the Musi River in Palembang. The method used by researchers is a descriptive method with a qualitative approach. Based on the results of research and discussion, safety standards for speedboat passengers in the Musi River flow area, there are several Minister of Transportation regulations that have not been implemented, such as emergency exits on large speedboats, the absence of traffic signs in the Musi River area which causes the speedboat driver to not know the state of the river like the presence of trees and stones in the water. Safety equipment such as life jackets or life jackets, and buoys amount to only around 10% per boat. There is no record of the passenger, the passenger pays the transportation fee directly to the driver.